2012
DOI: 10.1017/s0029665112001577
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in elite Irish athletes

Abstract: Recent evidence suggests that vitamin D insufficiency is associated with an increased risk of stress fracture, total body inflammation, infectious illness and impaired muscle function (1,2) and is thus likely to impair the training ability of athletes in addition to affecting their overall health. Though not widely studied, vitamin D deficiency and insufficiency have been reported among athletes, irrespective of geographic location (3) . The aim of the current study was to assess vitamin D status in two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Calcium and vitamin D have roles in bone-building and muscle strength and function [ 19 , 20 , 21 , 22 ]. Females did not meet the recommendation for calcium on average, and neither gender met the recommendations for vitamin D from diet alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium and vitamin D have roles in bone-building and muscle strength and function [ 19 , 20 , 21 , 22 ]. Females did not meet the recommendation for calcium on average, and neither gender met the recommendations for vitamin D from diet alone.…”
Section: Discussionmentioning
confidence: 99%
“…Females did not meet the recommendation for calcium on average, and neither gender met the recommendations for vitamin D from diet alone. Others have reported insufficient serum vitamin D levels in up to 51% of Canadian and US Paralympic athletes [ 23 ] and 27% of Irish Paralympic athletes [ 22 ], depending on the season. A study looking at Swiss elite wheelchair athletes reported a high frequency of vitamin D deficiencies all year round; however, deficiencies were greater in the winter and for indoor sports [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our study results, vitamin D deficiency and iron deficiency was found in the diet and body of the deaf women athletes. Similarly, low serum vitamin D levels have been found in healthy and disabled athletes in other countries such as Canada, Swiss, and Ireland [21][22][23]. It should be noted that the serum concentration of 25(OH)D is the best indicator of vitamin D status.…”
Section: Discussionmentioning
confidence: 88%
“…However, the insufficient consumption of vitamin D with food remains one of the most pressing nutritional problems in athletes, especially in the athletes with disabilities. Moreover, clinical trials show a lack of an active form of vitamin D in athletes’ serum [ 21 , 22 , 23 ]. The deficiency of iron storage in the body leads to anaemia and the deterioration of aerobic capacity of athletes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate intakes of calcium and iron are common in females ( 3 ) , with inadequate iron intakes previously documented in female team sports ( 4 ) . Vitamin D insufficiency is also evident in male Gaelic footballers but has yet to be examined in females ( 5 ) . Therefore, the aim of this study was to evaluate calcium, iron and vitamin D intakes of club and county female Gaelic footballers, and compare them to recommended dietary allowances (RDAs) ( 2 ) .…”
mentioning
confidence: 99%